The Role of Transformative Innovation for SDGs Localisation. Insights from the South-African "Living Catchments Project". Issue 4 (2nd October 2021) - Boni, Alejandra; Velasco, Diana; Tau, Mahlodi
ABSTRACT : The 2030 Agenda positioned Science, Technology and Innovation as crucial means for achieving the Sustainable Development Goals (SDGs). This paper explores how a localised South-African policy experiment named the "Living Catchments Project" (LC Project) contributes towards the SDGs. This project is part of a portfolio of experiments to trigger innovation for transformative change in South Africa. The LCP team worked directly with the Transformative Innovation Policy Consortium (TIPC) researchers adding a transformative layer to the project's design and implementation. The project embraces uncertainty and complexity by promoting experimentation to inform and facilitate learning processes and changes in people, organisations and institutions. Additionally, we combine the TIP perspective with core concepts of the capability approach: capabilities, agency, democratic deliberation and conversion factors. With this integrated approach, we explore what the capability approach can offer to the LC Project. We conclude with policy recommendations on the potentialities and constraints of the combined TIP- capability approach for achieving the SDGs and conducting transformative innovation experiments.